Aortoesophageal Fistula Caused by Descending Aortic Pseudoaneurysm - Mahmood, Shagufta; Hossain, M Motahar; Hossain, M Akhter (Journal of Bangladesh College of Physicians and Surgeons, 2017)
A 60 year old man presented in Square Hospitals LTD with hypovolaemic shock,and massive haematemesis.His BP was non-recordable with soft , non-tender abdomen and Hb was 8g/dl with normal prothrombin time and partial thromboplastin time and normal platelets .By endoscopy and CT scans aortoesophageal fistula with aortic pseudoaneurysm was identified and immediate surgery was done with complete occlusion of the pseudoaneurysm ,which was confirmed by repeat CT scan. J Bangladesh Coll Phys Surg 2017; 35(1): 34-35